Instructional Tools for Online Physical Education: Using Mobile Technologies to Enhance Learning. Issue 6 (24th July 2019) - Goad, Tyler; Towner, Brooke; Jones, Emily; Bulger, Sean
Abstract : The growth of the Internet and related technologies has resulted in changes in education and society that have placed new demands on teachers. Online physical education (OLPE) presents a unique set of challenges in translating traditional face-to-face courses to a digital space. The delivery of OLPE has been met with skepticism, given the inherent difficulty in conceptualizing the effective instruction and assessment of physical activity in an online setting. Despite these concerns, OLPE continues to become more prevalent. Most states now allow physical education credits to be earned online and have passed legislation mandating completion of an online course, regardless of subject, as a high school graduation requirement. It is critical that physical educators who are providing these learning experiences develop proficiency in online pedagogy and the use of supporting technologies. The purpose of this article is to describe the functionality of innovative technologies for use in OLPE, including recommendations for their integration into professional practice. The features, functions and potential applications of physical activity/fitness trackers, mobile fitness applications, and mobile exergames are discussed.